Creating Resilient Futures Integrating Disaster Risk Reduction, Sustainable Development Goals and Climate Change Adaptation Agendas - Flood, Stephen; Jerez Columbié, Yairen; Le Tissier, Martin; O'Dwyer, Barry (Springer Nature, 2022)
This open access edited volume critically examines a coherence building opportunity between Climate Change Adaptation, the Sustainable Development Goals and Disaster Risk Reduction agendas through presenting best practice approaches, and supporting Irish and international case studies. The Covid-19 pandemic has highlighted existing global inequalities and demonstrated the scope and scale of cascading socio-ecological impacts. The impacts of climate change on our global communities will likely dwarf the disruption brought on by the pandemic, and moreover, these impacts will be more diffuse and pervasive over a longer timeframe. This edited volume considers opportunities to address global challenges in the context of developing resilience as an integrated development continuum instead of through independent and siloed agendas.